Mixtures development, physicochemical characterization, and consumer acceptance for high-protein vegan burgers based on pre-gelatinized grains flours without gluten - FERREIRA, Bruna Mayara Roldão; TORRES, Isadora Maria Melo; MONTEIRO, Antonio Roberto Giriboni (Food Science and Technology, 2024)
Veganism is on the rise as a major trend in today’s world. Plant proteins are gaining popularity as substitutes for animal proteins, given their versatility across various sources. It is believed that blending complementary protein sources in modern analog products can offer a balanced nutrient profile. To provide vegan consumers with a convenient and nutritious plant-based protein option, three different powder formulations of vegan burgers were developed using gluten-free pre-gelatinized flours (MIX 1, MIX 2, and MIX 3), carrying out physicochemical characterization and consumer acceptance. Samples 1 and 2 showed notably high levels of crude protein (17.99 and 18.09), surpassing previous studies. Hardness (N) ranged from 6.66 to 8.41, with no significant differences observed, suggesting that the stiffness of grains used did not impact this parameter. While sensory analysis did not yield significantly different results across attributes like color, taste, flavor, and texture, overall preference favored sample 3 (49%). The formulation containing sorghum (Sorghum bicolor) and pea isolate (Pisum sativum), unlike others, likely contributed to its higher acceptance.